Effect of anastrozole on hormone levels in postmenopausal women with early breast cancer. (February 2015) - Kyvernitakis, I.; Albert, U-S.; Kalder, M.; Winarno, A-S.; Hars, O.; Hadji, P.
Abstract Objectives The aim of this study was to investigate the influence of anastrozole on serum hormone levels in postmenopausal women with hormone receptor-positive breast cancer. Methods We prospectively determined serum levels of estradiol, testosterone, dehydroepiandrosterone sulfate (DHEAS), sex hormone binding globulin (SHBG), follicle stimulating hormone (FSH) and luteinizing hormone (LH) at screening, as well as after 12 and 24 months of treatment and studied the associations with markers of bone turnover and bone mineral density (BMD). Results Altogether, a full set of hormone levels was available for 70 patients. Anastrozole treatment led to decreases of 92.1% for estradiol and 11.1% for LH over the observation period (p < 0.001). Conversely, FSH, DHEAS and testosterone concentrations increased by 5.9%, 33.3% and 50%, respectively (p < 0.001). SHBG levels remained stable during the 24 months of treatment (p = 0.355). There were modest associations between FSH, SHBG, CrossLaps and N-terminal propeptide of human procollagen type I (p < 0.05). Moreover, SHBG correlated positively with the BMD of femoral neck, total hip, total hip T-score, lumbar spine and the lumbar spine T-score, whereas FSH and estradiol correlated with the lumbar spine T-score (p < 0.05). Conclusions During the 24 months of follow-up, treatment with anastrozole decreased the serum levels of estradiol and LH. Furthermore, we found notable increases of serum levels of FSH, DHEAS and testosterone in the first 12 months of treatment, stabilizing thereafter. Additionally, we were able to correlate hormone levels with markers of bone turnover and BMD for the first time in this regard.